The relationship between risk factors and speech-language disorders in children aged four to six years - Jelena Tešić; Mile Vuković; Mirjana Korlaet; Sofija Vuković (Биомедицинска истраживања, 2023)
Introduction: In recent years, more and more attention has been paid to the research of factors that can potentially contribute to the development of speech and language impairment. It is believed that the results of these studies can contribute to better planning and implementation of early intervention in the field of speech and language in children. The aim of this research is to determine the influence of risk factors on the appearance of language disorders in children. Methods: A total of 97 children aged four to six who participated in the research were divided into two groups. The first group consisted of 54 respondents with a speech and language impairment, and the second group consisted of 43 respondents with typical language development. In both groups, 70 children with risk factors were found. All children with speech and language impairment had some of the risk factors (diseases of mothers during pregnancy, medication during pregnancy, premature labor, caesarean section, asphyxia, disease of newborns, seizures, third tonsil, shortened frenulum, ear infection), while in the group of children with typical language development, 16 respondents had risk factors. The Global Articulation Test, Vocabulary Test, and Comic Story Test were used to assess speech and language abilities. Data on risk factors were obtained on the basis of a survey for parents, which was constructed for the purposes of this research. Results: The results showed that children with risk factors had significantly worse results on the articulation test and the vocabulary test compared to children without risk factors. The results obtained on the Strip Story test did not show that these two groups differ significantly in terms of the number of words produced, the number of sentences and the grammatical structure of the sentence. Conclusion: In general, the results of this research showed a significant connection between risk factors and speech and language disorder in children.
Keywords: risk factors; speech-language impairment; articulation; vocabulary; syntax